Analysis of method stability of slope failure using slope/w and manual calculation for redesigning failed slope - a case study - Anshana Suwanno, Tan (2019)
Slope failure have become one of the most natural disasters that commonly happened in Malaysia due to many factors. The rising of the landslide cases, natural disasters, and the demand for engineered cut and fill slopes on development and construction projects in Malaysia also developed the commitment to improve the understanding and principles of soil mechanics that connect soil behavior to slope stability, investigative tools, the analytical methods and stabilization method or remedial measures involved to deal with slope stability issue. This paper will focus more on the slope stability analysis using the Ordinary Method of Slices with approaching using software Slope/W and manual calculation. The data and soil parameters were basically based on a real case study of a failed slope that happened at Taman Bukit Kuchai, Bandar Kinrara, Selangor Dahrul Ehsan which have failed and may cause further failure and effect to the residents around the area in the future. With the analysis and computing of factor of safety, comparison between both methods can be compared, the causes of slope failure can be identified, hence remedial measures can be applied to the failed slope. From the analysis it is found that, the slope at Taman Bukit Kuchai, Bandar Kinrara, Selangor Dahrul Ehsan is considered as failed. With the analysis and computing of factor of safety, the FOS value obtained is 1.060 which is considered as unsafe and unstable. FOS value computed using Ordinary Method of Slice by using Software Slope/W (1.060) and manual calculation (1.1507) is similar to each other. Hence, it shows that both methods have same FOS value due to apply same formula (Fellenius’s method) to analyze the slope. Based on soil investigation report, the slope failed may be due to the type of soil which has low strength may cause the potential block slide downward due to its discontinuities parameter, triggered by severe erosion and intense rainfall. Comparing with other remedial measures to stabilize the slope in term of FOS value, the best remedial measures to be selected after considering the highest FOS value of 2.167 is soil nails. It shows that by applying this type of remedial measures, the FOS value have increase by 51.08%.